2009
DOI: 10.1007/978-3-642-00528-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Mining Research Communities in Bibliographical Data

Abstract: Abstract. Extracting information from very large collections of structured, semistructured or even unstructured data can be a considerable challenge when much of the hidden information is implicit within relationships among entities in the data. Social networks are such data collections in which relationships play a vital role in the knowledge these networks can convey. A bibliographic database is an essential tool for the research community, yet finding and making use of relationships comprised within such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Besides the network property analysis there is an interest in research related to the topic development and distribution in scientific community. Zäine, Chen and Goebel [21] used collaboration network embedded in DBLP to discover topical connections between the network members and eventually use them in a recommendation system. Another investigation connecting topics and co-authors community has been reported in [22].…”
Section: Related Workmentioning
confidence: 99%
“…Besides the network property analysis there is an interest in research related to the topic development and distribution in scientific community. Zäine, Chen and Goebel [21] used collaboration network embedded in DBLP to discover topical connections between the network members and eventually use them in a recommendation system. Another investigation connecting topics and co-authors community has been reported in [22].…”
Section: Related Workmentioning
confidence: 99%
“…From the literature work, it is evident that identify the target customers is essential to retain the customers for ecommerce sites. It is also evident that the better clustering will provide more accurate predication for identifying user's behavioral pattern [4][5]. It is inferred from the research work that the target customer is identified by different clustering techniques.…”
Section: Motivation Of This Researchmentioning
confidence: 95%
“…In addition, citation graphs provide useful statistical information. For example, a set of journal/proceedings (or authors) can be grouped by using clustering algorithms (Biryukov & Dong, 2010;Zaane, Chen, & Goebel, 2009;Zhou, Ji, Zha, & Giles, 2006). Another branch of previous work focuses on finding the most important journal/proceedings (or authors) in the sense of citation (Nerur, Sikora, Mangalaraj, & Balijepally, 2005;Yan & Lee, 2007).…”
Section: Related Workmentioning
confidence: 99%